Human recombinant domain antibodies against multiple sclerosis antigenic peptide CSF114(Glc). Issue 10 (1st August 2014) - Niccheri, Francesca; Real‐Fernàndez, Feliciana; Ramazzotti, Matteo; Lolli, Francesco; Rossi, Giada; Rovero, Paolo; Degl'Innocenti, Donatella
<x xml:space="preserve">Abstract</x> Multiple sclerosis (MS) is a chronic auto‐immune disease characterized by a damage to the myelin component of the central nervous system. Self‐antigens created by aberrant glycosylation have been described to be a key component in the formation of auto‐antibodies. CSF114(Glc) is a synthetic glucopeptide detecting in vitro MS‐specific auto‐antibodies, and it is actively used in diagnostics and research to monitor and quantify MS‐associated Ig levels. We reasoned that antibodies raised against this probe could have been relevant for MS. We therefore screened a human Domain Antibody library against CSF114(Glc) using magnetic separation as a panning method. We obtained and described several clones, and the one with the highest signals was produced as a 6×His‐tagged protein to properly study the binding properties as a soluble antibody. By surface plasmon resonance measurements, we evidenced that our clone recognized CSF114(Glc) with high affinity and specific for the glucosylated peptide. Kinetic parameters of peptide–clone interaction were calculated obtaining a value of KD in the nanomolar range. Harboring a human framework, this antibody should be very well tolerated by human immune system and may represent a valuable tool for MS diagnosis and therapy, paving the way to new research strategies. Copyright © 2014 John Wiley & Sons, Ltd.